The influence of tourist facilities that affect satisfaction and loyalty on the beach gili genting sumenep district - Nina Wulandari; Nurita Andriani (Institute of Computer Science (IOCS), 2023)
This research aims to analyze the influence of tourist facilities on the level of satisfaction and loyalty of visitors at Gili Genting Beach, Sumenep Regency. Gili Genting Beach is a tourist destination that has the potential to increase local tourism, but it is necessary to understand more deeply how the facilities available at this beach influence visitors' perceptions and behavior. The research method uses a quantitative approach by collecting data through questionnaires distributed to visitors to Gili Beach Genting. Data analysis was carried out using multiple linear regression techniques to identify the relationship between tourist facility variables, visitor satisfaction and visitor loyalty using Smartpls 4 software using 100 test data from the results of distributing questionnaires. The research results show that tourist facilities such as accessibility, service quality, supporting facilities (toilets, eating places and play areas), and beach cleanliness have a significant influence on the level of visitor satisfaction. Apart from that, visitor satisfaction also has a positive impact on their loyalty to Gili Genting Beach. These findings provide valuable insights for managers and stakeholders in developing Gili Genting Beach as a more attractive and sustainable tourist destination. By improving existing tourist facilities and ensuring a satisfying visitor experience, Gili Genting Beach can gain more loyal visitors and has the potential to contribute to local economic growth